Захист прав кредиторів спадкодавця у сфері спадкового права - Кухарєв, О. Є.; Kukharev, O. Y.; ORCID: http://orcid.org/0000-0003-2086-9179 (Право і суспільство. - 2020. - № 6/2, ч. 1. - С. 76-81, 2020)
Проаналізовано питання захисту прав кредиторів спадкодавця у сфері спадкового права. Обґрунтовано, що кредитор спадкодавця наділений правовою можливістю застосувати як спеціальний спосіб захисту, що полягає у зверненні стягнення на майно, яке було передане спадкоємцям у натурі, так і загальні способи захисту цивільних прав та інтересів судом, закріплені у ст. 16 ЦК. Таке розуміння захисту прав цього суб’єкта не порушує справедливого балансу між законними інтересами і правомірними очікуваннями кредитора та зустрічними їм інтересами спадкоємців. Наголошено на тому, що звернення стягнення на успадковане майно не завжди є ефективним способом захисту, а його доцільність залежить передусім від складу спадщини. Підкреслено, що право власності на незначну частку у квартирі або житловому будинку буде вкрай важко реалізувати кредиторові задля погашення боргів спадкодавця.

The author of the article has analyzed the issue of protecting the rights of ancestor’s creditors in the field of inheritance law. It has been substantiated that the ancestor’s creditor is endowed with the legal opportunity to apply both a special method of protection, which is to recover property that was transferred to the lawful heirs in kind, and general methods of protection of civil rights and interests by the court enshrined in the Art. 16 of the Civil Code. Such understanding of the protection of the rights of this entity does not violate the fair balance between the legitimate interests and legitimate expectations of the creditor and the counter-interests of the lawful heirs. It has been emphasized that recovery proceedings against inherited property are not always effective method of protection, and their expediency primarily depends on the composition of the assets. It has been noted that the ownership of a small share of an apartment or house will be extremely difficult to exercise for the creditor in order to repay the debts of the ancestor. The rights of the creditor are subject to judicial protection only if certain conditions are met, namely: presentation by the creditor of a written claim to the lawful heir to repay the debts of the ancestor; compliance with the terms for filing such a claim; acceptance of the assets by the lawful heir in the manner and terms specified by civil law; the lawful heir’s non-fulfillment of the obligation to satisfy the creditor’s claims through a one-time payment. In case of protecting the rights of the ancestor’s creditor within court proceedings, the debtor’s lawful heirs are additionally charged with court costs, which consist of court fees and expenses related to court hearings. Herewith, the amount of court costs is not taken into account while calculating the amount of debts of the ancestor to be paid by the lawful heirs. This means that the ancestor’s debt is collected from the lawful heir within the value of the inherited property, and additional amount of court costs incurred by the creditor while applying to the court.

Проанализированы вопросы защиты прав кредиторов наследодателя в сфере наследственного права. Обосновано, что кредитор наследодателя наделен правовой возможностью применить как специальный способ защиты, заключающийся в обращении взыскания на имущество, переданное наследникам в натуре, так и общие способы защиты гражданских прав и интересов судом, закрепленные в ст. 16 ГК.
Protecting the rights of ancestor’s creditors in the field of inheritance law
Кухарєв, О. Є. Захист прав кредиторів спадкодавця у сфері спадкового права / Кухарєв О. Є. // Право і суспільство. - 2020. - № 6/2, ч. 1. - С. 76-81. - DOI: https://doi.org/10.32842/2078-3736/2020.6.2.1.12.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Спадкове право. Inheritance law. Наследственное право; спадкування; inheritance; наследование; кредитор спадкодавця; creditor of the testator; кредитор наследодателя; борги спадкодавця; debts of the testator; долги наследодателя; спадкодавець; testator; наследодатель; захист прав кредитора; protection of the creditor's rights; защита прав кредитора